The Influence of Financial Literacy on Investment Decision-Making Among Generation Z - Mawarni, Resky Cyntia; Hendrawaty, Ernie (LPPPIPublishing, 2025)
The low level of financial literacy among Generation Z has the potential to lead to irrational investment decisions and increase the risk of being involved in illegal investments. This study aims to analyze the effect of financial literacy and financial knowledge on investment decisions, with financial behavior as a mediating variable. The research sample consisted of 160 Generation Z respondents aged 18–28 years who had an interest in or experience with stock investment. The sampling technique used was purposive sampling. Data were analyzed using path analysis and the Sobel test. The results indicate that financial literacy and financial knowledge have a positive and significant effect on both financial behavior and investment decisions. Furthermore, financial behavior significantly mediates the relationship between financial literacy, financial knowledge, and investment decisions.